INDIA’S CYBERSECURITY DIPLOMACY: BUILDING GLOBAL ALLIANCES - Chaudhary, Pramod Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The emerging interconnection and interdependence of the world, cyberspace has become an indispensable domain that shapes national security, economic growth and stability of the world. With India now emerging as a rising global power and global digital leader, it has catapulted cybersecurity diplomacy as its centrepiece of international agendas. This paper looks at India's attempts at developing global alliances and advancing multilateralism in positioning itself to respond to cyberspace challenges. India’s cybersecurity diplomacy exists at different levels. It is a convinced advocate in multilateral platforms such as the United Nations for norms governing state behavior in cyberspace and for a rules based global order. India works in regional cooperation with South Asian and ASEAN partners in regard to cyber resilience and capacity building initiatives. It has been brokering strong cybersecurity partnerships bilaterally with countries including the United States, Japan, Australia and the European Union on the basis of reciprocal threat intelligence sharing, joint exercises, technological innovation. An additional member of the Quad, India is involved in Indo-Pacific cyber security initiatives seeking to protect critical infrastructure and foster digital inclusivity. India has domain civil cybersecurity defenses and imparted the capacities to a relative through CERT–In and NCIIPC, investment in capacity building programming and public private party ties to the expansion within India’s technological abilities. India maintains that the balancing of cyber sovereignty with principles of an open and secure internet should follow by respecting equitable data governance frameworks and inclusive international standards. But geopolitical tensions, advanced cyber threats, and fast-moving technology still exist. As a proactive player in India’s diplomacy, its form in shaping global cyber governance plays a leading role. India is working to develop a secure digital ecosystem by creating trust, transparency and collaboration, to drive a peaceful, innovative and shared prosperity in the era of unprecedented digital transformation.